Determinant Analysis of Stock Price Study at Property and Real Estate Companies Listed in Indonesia Stock Exchange - Harsono Putra, Rahmadeka Dwian; Ira Setiawati,; Rita Meiriyanti, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aimed to analyze the effect of the variables Liquidity Ratio proxied by Current Ratio (CR), Solvability Ratio proxied by Debt to Equity Ratio (DER) and Profitability Ratio proxied by Return on Assets (ROA) and Return on Equity (ROE) among property and real estate companies listed in Indonesia Stock Exchange. The research population was all of the property and real estate companies listed in Indonesia Stock Exchange in the period of 2019-2023 amount 92 property and real estate companies. The sample selection technique used purposive sampling method. Based on certain criteria, there were 16 property and real estate companies that matched with sample. The data was analyzed by Multiple Linier Regression Method. The result of this research showed that Return on Equity had positive influence and significant on Stock Price. Current Ratio, Debt to Equity Ratio and Return on Assets had negative influence and significant on Stock Price. Liquidity Ratio, Solvability Ratio and Profitability Ratio could explain Stock Price by 0,360 or 36% and remaining 64% was explained by other variables outside the research model.